TRLS-07. BRAINSTORM: OUTCOMES FROM A MULTI-INSTITUTIONAL PHASE I/II STUDY OF RRx-001 IN COMBINATION WITH WHOLE BRAIN RADIATION THERAPY FOR PATIENTS WITH BRAIN METASTASES. (12th August 2019) - Kim, Michelle; Parmar, Hemant; Schipper, Matthew; Devasia, Theresa; Aryal, Madhava; Kesari, Santosh; O'Day, Steven; Morikawa, Aki; Spratt, Daniel; Junck, Larry; Mammoser, Aaron; Hayman, James; et al.
Abstract: INTRODUCTION: To determine the recommended Phase II dose of RRx-001, a radiosensitizer with vascular normalizing properties, when used with whole-brain radiation therapy (WBRT) for brain metastases, and to assess whether quantitative changes in perfusion MRI after RRx-001 correlate with response. METHODS AND MATERIALS: Five centers participated in this phase I/II trial of RRx-001 given once pre-WBRT then twice weekly during WBRT (30 Gy/10 fractions). Four dose levels were planned (5 mg/m2, 8.4 mg/m2, 16.5 mg/m2, 27.5 mg/m2). Dose-escalation was managed by the Time-to-Event Continual Reassessment Model (TITE-CRM). Correlative DCE-MRI was performed in a subset of patients and linear mixed models used to correlate change in 24-hour T1, Ktrans (capillary permeability) and Vp (plasma volume) with change in tumor volume. RESULTS: Between 2015–2017, 31 patients were enrolled. Two patients dropped out prior to any therapy and 7 were treated with concurrent temozolomide following a study amendment. Median age was 60 years (range, 30–76) and 17 were male. The most common tumor types were melanoma (58%) and non-small cell lung cancer (20%). No dose-limiting toxicities were observed. The most common severe adverse event was grade 3 asthenia in 6.9% (2/29). The median intracranial response rate was 46% (95%CI 24–68) and median overall survival was 5.2 months (95%CI 4.5–9.4). No neurologic deaths occurred. Among 10 evaluable patients undergoing DCE-MRI, a reduction in Vp 24 hours after RRx-001 was associated with reduced tumor volume at 1 month and 4 months (p≤0.01). CONCLUSION: The addition of RRx-001 to WBRT is safe and well-tolerated with favorable intracranial response rates. Because activity was observed across all dose levels, and in the absence of a dose response, the recommended Phase 2 dose is 10 mg administered twice weekly. A reduction in Vp by DCE-MRI 24 hours after RRx-001 suggests anti-angiogenic activity that is associated with longer-term tumor response.